Two particle green functions and nuclear structure - Mulhall, Walter; Liotta, Roberto; Evans, J. A.; Perazzo, R. P. J. (North Holland Publishing, 1967)
Fil: Mulhall, Walter Comisión Nacional de Energía Atómica; Argentina